2004
DOI: 10.1097/00126334-200404150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Race/Ethnicity With HIV Prevalence and HIV-Related Behaviors Among Young Men Who Have Sex With Men in 7 Urban Centers in the United States

Abstract: Using data from a multisite venue-based survey of male subjects aged 15 to 22 years, we examined racial/ethnic differences in demographics, partner type, partner type-specific condom use, drug use, and HIV prevalence in 3316 US black, multiethnic black, Latino, and white men who have sex with men (MSM). We further estimated associations of these factors with HIV infection and their influence on racial/ethnic disparities in HIV prevalence. HIV prevalences were 16% for both black and multiethnic black participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
162
6
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(177 citation statements)
references
References 39 publications
8
162
6
1
Order By: Relevance
“…13 Still, 19% of Black MSM reporting UAS in the past 12 months engaged in serodiscordant UAS during their last sexual encounter with a Black nonmain male partner. Whereas prior research has shown that elevated rates of sexual risk behavior alone may not account for elevated HIV seroprevalence rates among Black MSM, 10,[12][13][14][15] findings from the current study further suggest that elevated rates of sexual mixing with other Black MSM also may not adequately account for higher rates of HIV among Black men. Most likely, a combination of behavioral risk, sexual partner mixing, and additional contextual factors provide the best explanation of elevated HIV rates among Black MSM.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…13 Still, 19% of Black MSM reporting UAS in the past 12 months engaged in serodiscordant UAS during their last sexual encounter with a Black nonmain male partner. Whereas prior research has shown that elevated rates of sexual risk behavior alone may not account for elevated HIV seroprevalence rates among Black MSM, 10,[12][13][14][15] findings from the current study further suggest that elevated rates of sexual mixing with other Black MSM also may not adequately account for higher rates of HIV among Black men. Most likely, a combination of behavioral risk, sexual partner mixing, and additional contextual factors provide the best explanation of elevated HIV rates among Black MSM.…”
Section: Discussioncontrasting
confidence: 97%
“…Possible explanations for racial disparities in HIV and STD incidence have included socioeconomic position and cultural factors, structural barriers in accessing health care, and differences in sexual behavior. [7][8][9][10][11] Although studies have consistently found higher HIV prevalence among Black MSM relative to MSM of other races/ethnicities, comparable or lower rates of sexual risk behavior (i.e., unprotected anal sex [UAS]) have been observed among Black MSM compared to White and/or Latino MSM, 10,[12][13][14][15] suggesting that behavioral risk factors for HIV infection alone do not sufficiently explain elevated rates of HIV among Black MSM. 12 One potential explanation for higher HIV infection rates-that the sexual networks of Black MSM place them at greater risk for HIV and STDs than the sexual networks of other MSM-has not yet been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harawa and colleagues found risky sex and drug use reported more frequently by Caucasian rather than Black YMSM, whereas Sifakis et al found race to be unassociated with risk behavior. 6,7 These findings suggest that understanding racial/ethnic disparities in HIV risk among YMSM requires inquiry about factors beyond risk behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies of urban youth have corroborated findings of higher HIV seroprevalence rates among YMSM of color, with rates for African Americans ranging from nine to 12 times those for Whites. 12,13 A review of published, well-controlled intervention studies aimed at decreasing the spread of HIV and other sexually transmitted infections (STIs) among adolescents suggests that programs focused on individual behavior (e.g., condom use) can reduce HIV/STI risk-associated behavior and theory-based determinants of such behavior. [14][15][16][17][18] It remains unclear, however, whether the effects are sustainable for the long term.…”
Section: Introductionmentioning
confidence: 99%